1997
DOI: 10.1086/310574
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Low-Energy Photon Spectra in Gamma-Ray Bursts

Abstract: We report evidence that the asymptotic low-energy power law slope alpha (below the spectral break) of BATSE gamma-ray burst photon spectra evolves with time rather than remaining constant. We find a high degree of positive correlation exists between the time-resolved spectral break energy E_pk and alpha. In samples of 18 "hard-to-soft" and 12 "tracking" pulses, evolution of alpha was found to correlate with that of the spectral break energy E_pk at the 99.7% and 98% confidence levels respectively. We also find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
253
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(273 citation statements)
references
References 17 publications
19
253
1
Order By: Relevance
“…This last point is particularly noteworthy. Crider et al (1997), Lloyd-Ronning & Petrosian (2002) and later Kaneko et al (2006) found a significant correlation between E p and α in the time-resolved spectra of several GRBs. Supported by our simulations, we point out the possibility that a parameter reconstruction effect is at work in addition to any intrinsic correlation between E p and α.…”
Section: Analysis Of the Gbm Datamentioning
confidence: 87%
“…This last point is particularly noteworthy. Crider et al (1997), Lloyd-Ronning & Petrosian (2002) and later Kaneko et al (2006) found a significant correlation between E p and α in the time-resolved spectra of several GRBs. Supported by our simulations, we point out the possibility that a parameter reconstruction effect is at work in addition to any intrinsic correlation between E p and α.…”
Section: Analysis Of the Gbm Datamentioning
confidence: 87%
“…The empirical correlations among time-resolved spectral parameters were examined for BATSE and Fermi/GBM samples (Crider et al 1997;Preece et al 1998;Lloyd-Ronning & Petrosian 2002;Kaneko et al 2006;Goldstein et al 2012). The most significant correlation is found between E peak and low-energy spectral index for the time-resolved spectra of individual bursts.…”
Section: Spectral Analysismentioning
confidence: 99%
“…To address the open issue of whether classical synchrotron radiation or modified processes operate during the prompt GRB phase, ACT will provide high S/N hard X-ray spectra with good time resolution, so that we can study the temporal hard-to-soft evolution (e.g., [24]), determine the detailed spectral shape below the peak in the socalled Band function, and follow its correlation with the photon flux.…”
Section: Gamma Ray Burstsmentioning
confidence: 99%